Employee Silence and Silence Antecedents: A Theoretical Classification. (July 2020) - Chou, Shih Yung; Chang, Tree
Given the pervasiveness of employee silence, this article explores different forms of employee silence and silence antecedents. In particular, this article classifies employee silence using two dimensions: the target's solicitation and the employee's decision basis of conscious silence desirability. Drawing on relevant literature, it is proposed that employee silence can be classified into three distinct forms: unsolicited predetermined employee silence, unsolicited issue-based employee silence, and solicited target-based employee silence. When considering antecedents of employee silence, we claim that unsolicited predetermined employee silence is an outcome of personality traits, that unsolicited issue-based employee silence is triggered by functional motives, and that solicited target-based employee silence is determined by social relationships and relational experiences. By investigating forms of employee silence, this article provides important implications for theory and managerial practice.